2008
DOI: 10.1016/j.asoc.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Human-competitive lens system design with evolution strategies

Abstract: Lens system design provides ideal problems for evolutionary algorithms: a complex non-linear optimization task, often with intricate physical constraints, for which there is no analytical solutions. This paper demonstrates, through the use of two evolution strategies, namely non-isotropic SA-ES and CMA-ES, as well as multiobjective NSGA-II optimization, the human competitiveness of an approach where an evolutionary algorithm is hybridized with a local search algorithm to solve both a classic benchmark problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…The results could be used to improve the GA for optimization problems in real life lens design[45].Gagné et al applied EAs to an optimization criteria with complex mechanical constraints. Their results showed that EAs are comparable to those obtained by humans[46].…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…The results could be used to improve the GA for optimization problems in real life lens design[45].Gagné et al applied EAs to an optimization criteria with complex mechanical constraints. Their results showed that EAs are comparable to those obtained by humans[46].…”
mentioning
confidence: 52%
“…al. [46] discovered that on a real-life imaging problem the EA lens showed better results by a factor of almost two and was four times more sensitive than the expert lens design for the 1990 monochromatic quartet [40]. Moreover, an EA can explore a lens system, which is similar to a design performed by experts.…”
Section: First Studies Of Ga In Lens Designmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason we choose CMA-ES here is that CMA-ES has been shown effective for difficult non-linear non-convex black-box optimization problems in continuous domains with anywhere from 3 to 100 variables. CMA-ES has yielded competitive results for local and global optimization [18,17,2] and is now a well-established method with many different application domains [12,27,19].…”
Section: Introductionmentioning
confidence: 99%
“…These disciplines are characterized by nonlinear, multiobjective dynamical systems that face major obstacles of getting stuck in nonoptimal solutions and premature convergence [20][21][22]. Metaheuristics is a class of powerful stochastic algorithms, which have been proved over the years as efficient and fast problem solvers [23][24][25]. Computational intelligence (CI) belongs to this class of metaheuristic search techniques [26][27][28].…”
Section: Introductionmentioning
confidence: 99%